Global Cyber Security Research Output (1998–2019): A Scientometric Analysis. Issue 2 (3rd April 2021) - Dhawan, S.M.; Gupta, B.M.; Elango, B.
ABSTRACT: The main aim of this paper is to analyze the global cyber security literature and to discover underlying trends and developments at the global, national, institutional, and individual level using bibliometric indicators. The publications and citations data for the study were sourced from the SCOPUS database published during 1998–2019. Over this period of 22 years, cyber security research registered a 46.41% growth with an average citation impact of 5.05 citations per paper. Nearly 15% of the total papers were funded by external agencies. The top 10 countries alone accounted for the bulk (76.52%) of output in the subject. The United States leads this list with the highest publication productivity (43.75% of global output). Canada leads the world in terms of relative citation index (1.47). International collaboration has been a major driver of growth in cyber security research. The paper lists most productive organizations, authors, and journals.